Predictive Value of Bazett-Corrected QTc for Chemotherapy-Induced Cardiotoxicity in Breast Cancer: A Retrospective Cohort Study - Maria Lerista; Firinda Soniya; Zeta Reihan Salsabila; Justian Ananda Putra; Vania Agustine; Syahri Banun; Muhammad Rizky Felani; Indah Puspita; Alexander Edo Tondas (The Indonesian Heart Association, 2026)
Background : Cardiotoxicity remains a major concern in breast cancer patients receiving anthracycline-based chemotherapy. Meanwhile, prolongation of the QTc interval has been associated with an increased risk of torsades de pointes; however, the clinical evidence for its role as a predictor of subclinical cardiotoxicity remains limited. This study aims to evaluate the association between Bazett-corrected QTc and the incidence of subclinical left ventricular dysfunction, as measured by strain echocardiography. Methods : This single-center retrospective cohort study was conducted at Dr. Mohammad Hoesin General Hospital, Indonesia (January 2022–December 2023). Female breast cancer patients aged ≥18 years who received anthracycline or non-anthracycline chemotherapy and completed baseline and third-cycle echocardiography were included. QTc was measured from 12-lead ECGs before and after chemotherapy using Bazett’s formula. Subclinical cardiotoxicity was defined as a >15% relative reduction in global longitudinal strain (GLS) from baseline. Logistic regression and ROC analyses assessed the predictive value of baseline QTcB. Result : In 32 breast cancer patients on anthracycline therapy (mean age 49.5 ± 9.0 years) were analyzed; 59.4% developed subclinical cardiotoxicity. Prolonged baseline QTcB, older age, and obesity were significantly associated with subclinical cardiotoxicity (p < 0.05). In multivariate analysis, QTcB remained an independent predictor (OR = 21.09; 95% CI: 0.979–454.4; p = 0.05). ROC analysis showed moderate discrimination (AUC = 0.717; 95% CI: 0.50–0.92; p = 0.04). Conclusion : Prolonged QTc appears to be a promising predictor of subclinical cardiotoxicity with fair diagnostic accuracy. However, it should be considered alongside other modalities. Further studies with larger populations are needed to control for other risk factors.